2022
DOI: 10.1186/s12879-022-07452-w
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of COVID-19 vaccination and influencing factors among people living with HIV in Guangxi, China: a cross-sectional survey

Abstract: Background Vaccination has been proven to be an effective approach against the coronavirus disease 2019 (COVID-19) pandemic. This study aimed to determine the acceptance rate and factors influencing acceptance of COVID-19 vaccination among people living with HIV (PLWH) in Guangxi, China. Methods A cross-sectional survey was carried out in five cities in Guangxi, China from May 7 to June 1, 2021. Questionnaires on the acceptance of COVID-19 vaccinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 34 publications
3
15
0
Order By: Relevance
“…What's more, 74.8% of the vaccinated patients did not want to receive another dose of COVID-19 vaccine mainly because of safety concerns. This is consistent with results from the general population and other population groups (24)(25)(26)(27). According to a survey study in Poland, 49.2% of the participants refused to receive a booster dose because of side effects experienced after previous doses, and 22.4% because of safety uncertainties (28).…”
Section: Discussionsupporting
confidence: 87%
“…What's more, 74.8% of the vaccinated patients did not want to receive another dose of COVID-19 vaccine mainly because of safety concerns. This is consistent with results from the general population and other population groups (24)(25)(26)(27). According to a survey study in Poland, 49.2% of the participants refused to receive a booster dose because of side effects experienced after previous doses, and 22.4% because of safety uncertainties (28).…”
Section: Discussionsupporting
confidence: 87%
“…Those who showed positive attitude towards the vaccine, have greater confidence in the vaccine, have better perceived behaviour to take up the vaccination and received other vaccinations in the past 3 years were more vaccine‐accepting [20, 22], whereas people with negative attitudes towards COVID‐19 vaccination, those who generally refused vaccine, those viewing vaccines as unsafe and ineffective for HIV patients and people who had concerns about side effects were less likely to accept COVID‐19 vaccination [19, 22, 23].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, Su et al performed a similar survey, but only within the HIV-positive participants, and concluded that the most important factors influencing acceptance were the perception that vaccination is unsafe for HIV-infected people (aOR = 0.082, 95% CI = 0.024–0.282) and the poor efficacy in preventing COVID-19 in HIV-positive persons (aOR = 0.093, 95% CI = 0.030–0.287). Other factors associated with acceptance included Zhuang ethnicity (aOR = 1.653, 95% CI = 1.109–2.465), a highest education level of middle school, high school, or above (aOR = 1.747, 95% CI = 1.170–2.608; aOR = 2.492, 95% CI = 1.326–4.682), and the vaccination having little effect on ART efficacy (aOR = 2.889, 95% CI = 1.378–6.059) [ 22 ]. Therefore, there are many issues that clinicians have to face in order to obtain immunity among the vast majority of the population and break the epidemiological chain of SARS-CoV-2 infections.…”
Section: Discussionmentioning
confidence: 99%